2016
DOI: 10.1016/j.solmat.2016.07.044
|View full text |Cite
|
Sign up to set email alerts
|

The optimal TiO2/Ag/TiO2 electrode for organic solar cell application with high device-specific Haacke figure of merit

Abstract: As a promising indium-free electrode, transparent composite electrode (TCE) TiO 2 /Ag/TiO 2 is an attractive alternative to indium tin oxide (ITO). The multilayer structure of TiO 2 /Ag/TiO 2 is deposited on glass substrate by room-temperature sputtering. The effects of deposition rate, thickness of Ag and TiO 2 layers on the electrical and optical properties of this TCE are presented. Results show that the Ag films tend to have fewer voids to form, if the Ag deposition rate is sufficiently high. The presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 27 publications
3
18
0
1
Order By: Relevance
“…Titanium dioxide (TiO 2 ) has been widely used in various technological applications such as photocatalytic layers [1], diodes [2], sensors [3], cosmetics [4] and solar cells [5]. Therefore, TiO 2 nanoparticles can be synthesized in order to use in diverse methods like laser ablation [6], RF thermal plasma [7], hydrothermal method [8], mechanochemical [9], the ultrasonic technique [10], metal organic chemical vapor deposition method [11] and sol-gel process [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) has been widely used in various technological applications such as photocatalytic layers [1], diodes [2], sensors [3], cosmetics [4] and solar cells [5]. Therefore, TiO 2 nanoparticles can be synthesized in order to use in diverse methods like laser ablation [6], RF thermal plasma [7], hydrothermal method [8], mechanochemical [9], the ultrasonic technique [10], metal organic chemical vapor deposition method [11] and sol-gel process [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…27 It has also been reported that the efficiency of photovoltaic devices can be improved by using oxide/metal/oxide electrodes, in contrast to simple oxide electrodes. 7,25,26 Therefore, it is believed that the gain in the efficiency of the solar cell is attributed to the improved optoelectrical characteristics, resulting from the optimum optical transmittance and charge carrier collections of the transparent conducting ACMA electrodes. These studies suggest that the device performance of CIGS solar cell can be signicantly improved by using the Cu-Mo composite layer with optimum thickness in contrast to a simple Cu or Mo metal layers stacked between AZO lms.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown the efficiency of photovoltaic devices have been signicantly improved by using oxide/metal/oxide based transparent conducting electrodes, in contrast to a simple oxide based electrodes. 7,25,26 Therefore, AZO/metal/AZO based transparent conducting lms with improved optical, electrical or structural properties promise an essential prerequisite for high efficient CIGS solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…In order to keep a low resistance and conversely maintain high optical transmittance, oxide-metal-oxide multilayered structures have recently received renewed interest as a highly promising route towards the production of flexible large area OLEDs and solar cells [3,[18][19][20]. In this case, Ag is the optimal metal because of its low resistivity (approximately 1.6 × 10 −6 Ω•cm) and relatively low cost [21], whereas Ga-doped ZnO (GZO) is the optimal oxide due to its abundance, low cost, superior optical features, and rather high stability [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Various deposition techniques have been used to produce oxide-metal-oxide structures, including thermal evaporation [24], electron beam evaporation [25], spray pyrolysis [26], sol-gel methods [27], ion beam sputtering [28], and magnetron sputtering [18][19][20]28]. Low-cost wet chemical methods are usually the starting point and benchmark for most academic and industrial processes that require a thin and uniform coating, but the transparent electrodes obtained by these techniques have resulted in inferior electrical features compared with those deposited by ion plasma methods [25,29,30].…”
Section: Introductionmentioning
confidence: 99%